Comparative Safety Analysis of Empagliflozin in Type 2 Diabetes Mellitus Patients with Chronic Kidney Disease versus Normal Kidney Function: A Nationwide Cohort Study in Korea - Ha Young Jang; In-Wha Kim; Jung Mi Oh (MDPI AG, 2023)
Background: Empagliflozin has been shown to reduce cardiovascular morbidity and mortality in patients with type 2 diabetes. Various research on its efficacy in patients with chronic kidney disease (CKD) have been actively conducted. So far, few studies have investigated the safety of these adverse effects specifically in Asians with CKD. We aim to address these safety concerns on a patient population of Asian CKD patients using real-world data. Methods: We conducted a retrospective cohort study using health insurance data from the Korean Health Insurance Review & Assessment Service and compared safety outcomes between empagliflozin and sitagliptin in 26,347 CKD patients diagnosed with diabetes. Adverse outcomes, including major adverse cardiac events (MACEs), all-cause mortality, myocardial infarction (MI), stroke, and hospitalization for heart failure (HHF), among others, were assessed. Results: Among a 1:1 matched cohort (6170 on empagliflozin, 6170 on sitagliptin), empagliflozin was associated with a significant reduction in MACEs, all-cause mortality, MI, hospitalization for unstable angina, coronary revascularization, HHF, hypoglycemic events, and urinary tract infections, but increased the risk of genital tract infections. No significant changes were observed for transient ischemic attack, acute kidney injury, volume depletion, diabetic ketoacidosis, thromboembolic events, and fractures. Conclusions: The usage of empagliflozin in diabetic CKD patients shows a significant reduction in many adverse outcomes compared to sitagliptin, but with an increased risk of genital tract infections. These findings provide evidence for future clinical decision-making around the use of empagliflozin in Asian CKD patients.